Гидродинамическое сопротивление поверхности со смешанными граничными условиями - Савченко, Ю.Н.; Семенов, Ю.А. (Видавничий дім "Академперіодика" НАН України, 2007)
The boundary layer near a solid wall, at which a sliding condition periodically appears, is considered. The problem is solved numerically using an explicit finite-difference method. The calculations are presented in terms of the velocity profile and the drag coefficient as functions of the Reynolds number and the scale factor of the sliding region. The obtained results show that a drag benefit increases with the scale factor of the sliding region. In order to reduce the drag force by two times, the total area of the sliding region should be no less than 70% of the total area of the wall.